Implementation Of Smarthome in The Property Industry (Case in Singkil Housing) - Fajar Hanggara Pratama; Syahrizal Dwi Putra; Verdi Yasin (Journal of Information System, Informatics and Computing, 2022)
With the advancement of technology, today the phenomenon of the industrial revolution 4.0 is born which collaborates with cyber technology and automation technology. With the revolution, the property industry is one of the industries that implemented this revolution, especially in housing in big cities. Discussing the application of 4.0 in the property industry which is still limited to big cities, it is known that houses in rural areas are still not experiencing the 4.0 industrial revolution. Research and application of 4.0 in rural houses is carried out by developing and implementing applications aimed at monitoring homes, Android-based applications and named Singkil, with the React Native programming language that implements IoT technology, which is one form of application of technology 4.0 . This research and application concludes that, the application of the Singkil application to homes can help homeowners in monitoring and controlling the situation of the house.